Trabeculectomy Under Augmented Topical Anesthesia: Study on Pain Evaluation and Surgical Feasibility. Issue 2 (March 2016) - Gupta, Sanjiv Kumar; Kumar, Ajai; Katiyar, Vishal; Agrawal, Siddarth
Abstract : Purpose: Performing trabeculectomy under topical anesthesia using lignocaine jelly with intracameral anesthesia may offer painless surgery with immediate visual gain and avoid the increase in intraocular pressure associated with locally injected anesthesia. In this context, we evaluated topical anesthesia using 2% lignocaine jelly with intracameral 1.0% lignocaine for trabeculectomy in terms of pain during surgery and the surgeon's experience. Design: This was a tertiary care center–based interventional case series. Methods: Patients scheduled for trabeculectomy as the first surgery for medically controlled glaucoma underwent standard ab externo trabeculectomy under topical anesthesia. Pain evaluation was done using a visual analog scale with the modified Wong-Baker FACES Pain Rating Scale, within 1 hour after surgery. Results: Fifteen eyes of 14 patients were included in the study with a mean (SD, range) age of 61.3 (17.54, 40–90, distributed normally) years. Patients' pain score analysis showed a mean (SD, range) visual analog scale score of 0.73 (0.59, 0–2) on a scale of 0 to 10. The mean (SD, range) surgeon's satisfaction score was 3.2 (0.4, 3–4) on a scale of 3 to 9. The intraocular pressure of all patients was well controlled at 2 weeks [mean (SD, range), 9.2 (2.9, 4–16)] and at 4 weeks [mean (SD, range), 13.2 (1.2, 11–15)] postoperatively without any topical or systemic antiglaucoma medications. Conclusions: Trabeculectomy can be done under augmented topical anesthesia, which provides adequate analgesia for acceptable patient and surgeon comfort with favorable outcomes. Anesthesia provided by topical application of lignocaine 2% jelly and intracameral 1.0% lignocaine is sufficient for safe trabeculectomy surgery with acceptable discomfort to the patient.